Precise control of the growth and size of Ni nanoparticles on Al2O3 by a MOF-derived strategy. Issue 44 (7th October 2019) - Li, Sha; Wang, Qianqian; Lu, Jingjun; Deng, Xiaonan; Bi, Shinan; Song, Zhiwen; Guo, Chao; Li, Ruifeng; Yan, Xiaoliang
Abstract : Homogeneous and small Ni nanoparticles are generated from a MOF-derived strategy, originating from the formation of surface NiAl2 O4 and the inherent confinement effect. Abstract : Precise synthesis of well-controlled metal nanoparticles on various supports is one of the most challenging issues in their applications for the sustainable production of fuels and chemicals. We herein propose an effective method to generate small Ni nanoparticles at a high loading content of 20 wt% with homogeneous dispersion on Al2 O3 regardless of low-temperature or high-temperature reduction. MIL-Al (110) was selected as the host for the fabrication of Ni nanoparticles with the size mainly at ∼5 nm after reduction at 600 or 800 °C. Conventional Al2 O3 loaded Ni with the same amount shows a different behavior, that is, the particle size of Ni nanoparticles increases from 12.5 ± 1.8 nm after reduction at 600 °C to 20.0 ± 2.4 nm after reduction at 800 °C. The formation of a surface NiAl2 O4 spinel structure on the Ni/Al2 O3 sample and the inherent confinement effect from pristine MIL-110 (Al) contribute to the stabilization of small Ni nanoparticles with a high loading content under different reduction conditions. These results will open a possibility of rationally designing and fabricating highly dispersed metal nanoparticles on certain supports.